Gender differences in the association between physical activity and obesity in adults with vision and hearing losses. (10th May 2021) - Pardhan, Shahina; Smith, Lee; Davis, Adrian; Bourne, Rupert; Barnett, Yvonne; Jacob, Louis; Koyanagi, Ai; Radzimiński, Łukasz; Skalska, Maria; Jastrzębska, Joanna; Jastrzębski, Zbigniew; López-Sánchez, Guillermo F
Abstract: Background: Physical inactivity is strongly associated with obesity, which in turn is a major risk factor for many non-communicable diseases. We examined associations between physical inactivity and obesity in Spanish adults with vision and hearing difficulties and explored differences between men and women. Methods: Data from the Spanish National Health Survey 2017 were analyzed [ n  = 23 089 adults (15–103 years, mean age 53.4 ± 18.9 years, 45.9% men)]. Participants self-reported difficulties in seeing and hearing. Physical inactivity (exposure) was evaluated with the International Physical Activity Questionnaire Short Form. Obesity (outcome) was defined as body mass index ≥30 kg m −2 based on self-reported weight and height. The association between physical inactivity and obesity was assessed with multivariable logistic regression in people with difficulties seeing and hearing, adjusting for significant covariates. Results: Multivariable logistic regression analyses showed that the association between physical inactivity and obesity was stronger in those with difficulty hearing (OR 1.778, 95% CI 1.215–2.602) compared with difficulty seeing (OR 1.375, 95% CI 1.076–1.756). Gender-stratified analyses showed significant association between physical inactivity and obesity in men who reported difficulty hearing (OR 2.319, 95% CI 1.441–3.735) and difficulty seeing (OR 1.556, 95% CI 1.079–2.244), but not in women. Conclusions: A significant association between physical inactivity and obesity was observed in Spanish men with vision and hearing difficulties. Physical activity has an important role in the prevention of obesity in men with seeing and hearing difficulties. Active steps should be taken to encourage physical activity to reduce the risk of obesity in people with sensory impairments.